2002
DOI: 10.1097/00126334-200208150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors in an Urban Bathhouse 15 Years Into the HIV Epidemic

Abstract: Although most bathhouse patrons engaged in lower risk activities, those reporting unprotected anal sex were more likely to report HIV infection and to have multiple sexual partners. Well into the HIV epidemic, bathhouses remain venues for ongoing spread of HIV and opportunities for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…In that regard, our findings suggest this intersection of risk profiles may also represent an important venue for public health interventions in sex party environments as a part of comprehensive HIV prevention. 25,36,37 Research has demonstrated that venue-based interventions can serve as viable and effective methods for reaching high-risk populations. [38][39][40] Our findings indicate that sex party attendees reported higher risk in a number of important individual factors such as sexual risk taking, drug use, intimate partner violence, and arrests, as compared with nonattendees.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, our findings suggest this intersection of risk profiles may also represent an important venue for public health interventions in sex party environments as a part of comprehensive HIV prevention. 25,36,37 Research has demonstrated that venue-based interventions can serve as viable and effective methods for reaching high-risk populations. [38][39][40] Our findings indicate that sex party attendees reported higher risk in a number of important individual factors such as sexual risk taking, drug use, intimate partner violence, and arrests, as compared with nonattendees.…”
Section: Discussionmentioning
confidence: 99%
“…Public sex venues such as bathhouses continue to be places where MSM, particularly HIV-positive MSM, engage in unsafe risk behavior. 17,18 Effective prevention efforts among HIV-positive MSM who frequent venues that promote anonymous sex are urgently needed. Likewise, the Internet continues to play an important role in disease transmission and presents a continuing challenge for adequate web-based health promotion and disease prevention for MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Grov et al [3] found that among patrons of SOP venues, 22% of their sample reported meeting half or more of their sex partners in such venues. While studies have found that few patrons of SOP venues engage in unprotected anal intercourse, patrons are more likely to be HIV positive and have greater numbers of partners while at the venue, facilitating HIV transmission [2,5]. Given this risk, public health officials have often argued for closing these venues [6].…”
Section: Introductionmentioning
confidence: 99%